Metode Tafsir Sosial Fazlur Rahman - Nabil Amir, Ahmad (Institut Agama Islam Hamzanwadi Pancor, 2022)
The paper examines the significance sociological ideas of Fazlur Rahman (1919-1988) and his methodological principles in interpreting the Qur’an which was laid out in his works, such as Major Themes of the Qur’an and Islam (University of Chicago Press, 1979). It attempts to set forth his modern and critical outlook of the Quran that formed his revisionist and contextualist approaches in his commentary and its essential textual understanding as derived from his major philosophical and religious works such as Prophecy in Islam: Philosophy and Orthodoxy (University of Chicago Press, 2011) Islamic Methodology in History, and Revival and Reform in Islam: A Study of Islamic Fundamentalism (Oneworld Publications, 1999). The basic principle of this methodology was structured from critical historical analysis and contextual and thematic approaches that formed his progressive outlook and modern worldview of the Quran with deep philosophical and theological reasoning and argumentative kalam viewpoints and dynamic ethical-legal principle and significance spiritual and moral foundation.